2013
DOI: 10.1063/1.4817934
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional labyrinthine acoustic metamaterials

Abstract: Building upon recent theoretical and experimental work on two-dimensional labyrinthine acoustic metamaterials, we design, fabricate, and characterize nearly isotropic three-dimensional airborne acoustic labyrinthine metamaterials. Our experiments on aluminum-based structures show phase and group velocities smaller than that of air by a factor of about 8 over a broad range of frequencies from 1 to 4 kHz. This behavior is in agreement with three-dimensional band-structure calculations including the first and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(107 citation statements)
references
References 13 publications
3
104
0
Order By: Relevance
“…Negative refraction was previously demonstrated using acoustic metamaterials based on space coiling [8,9], the drawbacks of these structures being their difficult fabrication in comparison with those studied here and their strong lossy characteristics [10]. Negative refraction was also demonstrated in phononic crystals with a fluid (liquid or air) matrix surrounding solid inclusions [11,12] and recently using a foamlike metallic structure [13].…”
Section: -2mentioning
confidence: 90%
“…Negative refraction was previously demonstrated using acoustic metamaterials based on space coiling [8,9], the drawbacks of these structures being their difficult fabrication in comparison with those studied here and their strong lossy characteristics [10]. Negative refraction was also demonstrated in phononic crystals with a fluid (liquid or air) matrix surrounding solid inclusions [11,12] and recently using a foamlike metallic structure [13].…”
Section: -2mentioning
confidence: 90%
“…The space-coiling design has not yet been demonstrated in water, where common solids such as steel that might be used to confine the coils cannot be assumed to be perfectly rigid due to their significantly smaller density contrast with water-thus introducing the challenge of elastic coupling [37] that must be incorporated into any design strategy. Although the kinematic viscosity of water is less than that of air [23], recent measurements of air-borne space-coiled metamaterials [36] demonstrate significant attenuation, and we caution that viscous effects should not be neglected in aqueous designs.…”
Section: Discussionmentioning
confidence: 99%
“…A class of metafluids based on the concept of space coiling have also featured prominently in the literature [33][34][35][36]. Space-coiled Fresnel lens designs are reported that show significant focusing while utilizing a thin aperture compared to the wavelength [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Since PCs were first proposed by Kushwaha et al, 2 much attention has been devoted to PCs because of their substantial applications in waveguide, 3 sound attenuation, 4 absorber, 5,6 sound insulation, 7 acoustic lens, 8 enhanced inertia, 9 shield, 10 filtering, 11,12 sensor, 13 strong reflectors for surface acoustic waves, [14][15][16] and microfluidic manipulations. 17,18 In addition, PCs give rise to novel effects, such as negative refraction, [19][20][21] negative birefraction, 22 negative elastic modulus, 23 and negative mass density.…”
Section: Introductionmentioning
confidence: 99%